2021
DOI: 10.3390/app11083501
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Based Airway Segmentation Using Key Point Prediction

Abstract: The purpose of this study was to investigate the accuracy of the airway volume measurement by a Regression Neural Network-based deep-learning model. A set of manually outlined airway data was set to build the algorithm for fully automatic segmentation of a deep learning process. Manual landmarks of the airway were determined by one examiner using a mid-sagittal plane of cone-beam computed tomography (CBCT) images of 315 patients. Clinical dataset-based training with data augmentation was conducted. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…All studies evaluated the accuracy of AI systems in segmenting and calculating airway volume based on CNN and RNN models. Three articles used their own model for software usage while one of the remaining two used the Mimics 19.0, InVivo 5 software and the other one the Diognocat, InVivo 5 software [26][27][28][29][30]. The procedure of article selection is presented on a flow diagram (Figure 1), and data are briefly presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…All studies evaluated the accuracy of AI systems in segmenting and calculating airway volume based on CNN and RNN models. Three articles used their own model for software usage while one of the remaining two used the Mimics 19.0, InVivo 5 software and the other one the Diognocat, InVivo 5 software [26][27][28][29][30]. The procedure of article selection is presented on a flow diagram (Figure 1), and data are briefly presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Following an extensive literature research, we have given the ICC values of 5 studies that compared the segmentation of AI and ground truth in Table 4 . ICC values were reported as 0.899 by Zhang et al 45 , 0.977 by Leonardi et al 46 , 0.985 by Sin et al 12 , 0.986 by Park et al 47 . Shujaat et al 48 provided precision, recall, accuracy, dice, intersection over union values in their study as 0.97 ± 0.01, 0.96 ± 0.03 1.00 ± 0.00 0.97 ± 0.02 and 0.93 ± 0.03, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…This limitation might affect the airway volume measurements as they have affected our segmentation process. The inconsistent head position of the patients, tongue, and breathing positions also cause errors in volumetric measurement, thus, scannings with controlling these possible limitations are required 47 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it only focused on the oropharynx but not on the nasopharynx. Some research reported automatic segmentation of the airway space with convolutional neural network on CBCT images [ 34 , 35 ]. We must admit that CBCT offers information on cross-sectional areas, volume, and 3D form that cannot be determined by cephalometric images.…”
Section: Discussionmentioning
confidence: 99%